Analisis Kaidah Al-Umuru Bi Maqasidiha dan Penerapannya dalam Ekonomi Islam - Indah Dwi Agustina Dewi; Raras Elok Manikam Putri Pribadi; Azka Nabilatuz Zahra; Zaskia Syafa Azizah; Salsabila Nur Syifa’; Naysila Khoirotun Nisa; Taufiq Kurniawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The principle of